The "Other" Geographies in Latin America: Alternatives from the Landscapes of the Chatino People - Geronimo Barrera de la Torre (Íconos)
This article focuses on "other" geographies, as understood through the spatial-temporal experiences of indigenous peoples. We argue that these experiences are equally valid subjective understandings of human-non-human relations and should be heard and valued within a framework of horizontal dialogue. This argument is based on research that was conducted in conjunction with the inhabitants of Chatina communities of San Juan Lachao in Oaxaca, Mexico. The research examined relations between humans, the landscape and other non-humans, that is, landscapes comprehended through the Chatino language, cosmological worldview, local knowledge and everyday life in Chatino territory. The theoretical and critical discussion we present is based on the study of the Chatino understanding of territory and landscape. Our critical and theoretical analysis draws on this understanding of landscape and points to the need to rethink and decolonize modernist constructions and make way for new epistemic and ontological understandings of human and other-than-human relations. We put forward alternatives that confront the dominant and unequal dynamics that persist in the production of knowledge in the field of critical geography.